2018
DOI: 10.1016/j.cortex.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Phase of beta-frequency tACS over primary motor cortex modulates corticospinal excitability

Abstract: The assessment of corticospinal excitability by means of transcranial magnetic stimulation-induced motor evoked potentials is an established diagnostic tool in neurophysiology and a widely used procedure in fundamental brain research. However, concern about low reliability of these measures has grown recently. One possible cause of high variability of MEPs under identical acquisition conditions could be the influence of oscillatory neuronal activity on corticospinal excitability. Based on research showing that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 55 publications
6
50
1
Order By: Relevance
“…EEG beta synchronizes with electromyography (EMG) from hand muscles during motor tasks, suggesting a crucial role in sensorimotor integration and connectivity 41,42 . Stimulating motor cortex activity with single-pulse TMS induces beta oscillations 43 and electrical stimulation at beta frequency (but not alpha) modulates motor cortex excitability 36,37 , in one case specifically for low-beta frequencies 44 , and can change connectivity patterns 45 .…”
Section: Discussionmentioning
confidence: 99%
“…EEG beta synchronizes with electromyography (EMG) from hand muscles during motor tasks, suggesting a crucial role in sensorimotor integration and connectivity 41,42 . Stimulating motor cortex activity with single-pulse TMS induces beta oscillations 43 and electrical stimulation at beta frequency (but not alpha) modulates motor cortex excitability 36,37 , in one case specifically for low-beta frequencies 44 , and can change connectivity patterns 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, it is of course possible that our null results are trivial; perhaps some aspects of our methodology were suboptimal to revealing tACS phase modulations which could have been obtained with larger samples or different experimental setup or design. We did validate the experimental approach itself (ten Oever, de Graaf et al, 2016), and recently used it to demonstrate beta-frequency tACS phase effects on motor-evoked potentials (Schilberg et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The goodness of fit would be reflected in R-squared; variance in datapoints explained by the sinusoid fit. Following previous reports (Fiebelkorn et al, 2011;ten Oever & Sack, 2015;Schilberg et al, 2018), we multiplied R-squared by the variance of the best-fitting sinusoid, to obtain relevance values. This hybrid measure reflects both the goodness-of-fit and the extent of modulation of performance by tACS, both of which are of interest in the current context.…”
Section: Analyses and Statistical Testsmentioning
confidence: 99%
“…For instance, tACS applied in the alpha and beta range was shown to lead to cyclic modulation of auditory, somatosensory or visual stimulus perception (20)(21)(22)(23). Further insight has been provided primarily in the motor domain, by showing tACS-phase-dependent changes in cortical excitability as measured by concurrent motor evoked potentials (24)(25)(26) or tACSinduced enhancement and phase cancellation of peripheral tremor in healthy subjects and patients with Parkinson's disease using closed-loop protocols (27)(28)(29)(30). Yet, latest findings by Asamoah et al (31) revealed that tACS-effects on the motor cortex are dominated by cutaneous stimulation of peripheral nerves in the skin leading to rhythmic activation of the sensorimotor system rather than by transcranial modulation of cortical tissue.…”
Section: Introductionmentioning
confidence: 99%